Notes on statistics of Argentine public universities: construction of enrolment, new students and graduate series, and observations on its evolution in the last five decades - Mariana Mendonça (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2020)
Statistical information is an essential input for carrying out any type of long-term analysis linked to university policy. However, in Argentina only since 1986 has the production of university statistics been based on a single source; previously, there is a multiplicity of sources with data that are often discordant. In this work we aim to construct as extensive series as possible of the data referring to enrollments, new students, and graduates of the public university system. This task has a twofold objective: on the one hand, to account for the general evolution of the system in the last 50 years; on the other hand, to make the constructed series available to other researchers. We conclude that the 1960s was a key decade to start to systematize statistics at this level, but that this process was affected by the constant restructuring of official agencies. It was not until 1983, with the consolidation of the democratic regime, that the data in question were collected in a more orderly manner. With these data, we have made an approximation to the construction of series on three of the most important indicators to analyze the general performance of the public system of national universities.